APOE Genotype Disclosure and Lifestyle Advice in a Randomized Intervention Study with Finnish Participants. Issue 1 (13th November 2020) - Leskinen, Heidi M; Tringham, Maaria; Karjalainen, Heli; Iso-Touru, Terhi K; Hietaranta-Luoma, Hanna-Leena; Marnila, Pertti J; Pihlava, Juha-Matti; Hurme, Timo; Kankaanpää, Santeri J; Puolijoki, Hannu; Åkerman, Kari; Tanner, Laura; et al.
ABSTRACT: Background: The APOE ε4 allele is associated with higher risks of cardiovascular diseases and Alzheimer disease than ε3 and ε2 . Objectives: We studied the effectiveness of dietary and lifestyle guidance and personal genetic risk information [ ε4 carrier (ε4+); ε4 noncarrier (ε4−)] as motivators for a healthier lifestyle. Methods: A total of 188 healthy Finnish volunteers (82.4% women; mean ± SD age: 51.0 ± 5.6 y; BMI: 26.0 ± 3.6 kg/m 2 ; total cholesterol: 5.2 ± 0.9 mmol/L) participated in our randomized intervention study. The participants were genotyped for APOE and divided into intervention (INT; INTε4+, n  = 33; INTε4−, n  = 57) and control groups (CTRL; CTRLε4+, n  = 36; CTRLε4−, n  = 62). Blood samples, measured observations, and questionnaire data were obtained at baseline and at 1 and 1.5 y. INT participants received their ε4 carrier status at baseline. Monthly Internet-based guidance based on the Finnish Dietary guidelines was provided for all. Results: The proportion of SFAs in plasma over time fluctuated less in INTε4+ than in the other groups ( P -interaction < 0.05; primary outcome). The lifestyle guidance increased vegetable consumption from 3.5 to 3.6 portions/d, improved the dietary fat quality score by 5.3%, increased the plasma n–3 (ω-3) FA proportion by 7.3%, and decreased the consumption of high-fat/high-sugar foods from 7.3 to 6.5 portions/wk and total- and LDL-cholesterol concentrations by 4.3% and 6.1%, respectively, in the entire participant population ( P < 0.05; secondary outcome). Compared with the ε4− participants, ε4+ participants had 2.4% higher plasma n–6 (ω-6) FA, lower C-peptide (3.9 compared with 4.2 nmol/L × h) and sensitive C-reactive protein values, and decreased plasma malondialdehyde concentrations over time ( P < 0.05; secondary outcome). Conclusions: Lifestyle guidance given to healthy Finnish participants yielded small but beneficial changes. The INTε4+ group did not seem markedly more responsive to the guidance than the other groups. This trial was registered at clinicaltrials.gov as NCT03794141.